I came out of the eighteenth century - Rice, John Andrew, 1888-1968 (Southern classics series., 2014)
"Memoir of the lifetime of John Andrew Rice. Combines crafty storytelling, historical witness, and ethical wisdom, and it should take a prominent place in the lineage of nonfiction Southern writing from Frederick Douglass to Zora Neale Hurston and Eudora Welty. Not least amongst its instruction is the overall trajectory of Rice's life, which he charted as a "spirit of opposition" whose "technique" improved as the years passed, estranging him from colleagues and straining friendships, but sustaining the precious capacity to see people and things plainly"--